The Use of STRONGkids, Total Lymphocyte Count, and Serum Albumin to Identify the Risk of Hospital Malnutrition in Children - Rusti, Hafiza Amadhin; Widjaja, Nur Aisiyah; Irawan, Roedi; Setiawan, Ariandi (Folia Medica Indonesiana, 2023)
Highlights: • Medium- and high-risk STRONGkids scores are related with low total lymphocyte count and serum albumin, which are related to hospital malnutrition, albeit indirectly. • The use of STRONGkids with total lymphocyte count and serum albumin can detect the risk of hospital malnutrition in children. Abstract: Hospital malnutrition occurs in hospitalized patients who do not consume enough food while their nutritional requirements increase. It occurs particularly in children who have undergone gastrointestinal surgery. Despite the lack of a universal instrument for detecting hospital malnutrition, various parameters can be considered to assist in its identification. STRONGkids has demonstrated its efficiency in detecting malnutrition risk in children. Total lymphocyte count (TLC) and serum albumin are biochemical markers that are related to infection and protein leakage, which can worsen hospital malnutrition. The research objective was to analyze the correlation between STRONGkids and biochemical markers (TLC, serum albumin) to identify hospital malnutrition in children who underwent gastrointestinal surgery. This was a retrospective cross-sectional observational study utilizing medical records. The statistical analysis was conducted using SPSS 21. This study included 37 subjects, with a 24.32% hospital malnutrition incidence rate. The subjects were divided into two groups: hospital malnutrition (n=9) and non-hospital malnutrition (n=28). The STRONGkids of both groups at admission demonstrated a significant difference, while the albumin and TLC did not. The significantly different STRONGkids scores of both groups at admission correlated negatively with the length of hospital stay (LOS), body weight reduction, TLC, and albumin. Those parameters also did not correlate with hospital malnutrition. However, hospital malnutrition increased the risk of low albumin and TLC at discharge by 2.951 and 5.549 times, respectively. In conlusion, TLC and serum albumin cannot be used as independent markers for hospital malnutrition, but STRONGkids can be used in conjunction with TLC and serum albumin to identify hospital malnutrition risk.